Systematics of the New Zealand longicorn beetle genus Oemona Newman with discussion of the taxonomic position of the Australian species, O. simplex White (Coleoptera: Cerambycidae: Ceram-bycinae) - Lu, Wen; Wang, Qiao (Zootaxa, 2005)
The New Zealand longicorn beetle genus Oemona Newman is revised. A diagnosis, a redescription of the genus, and a key to all species are given. Four known species, O. separata Broun, O. simplicicollis Broun, O. hirta (Fabricius) and O. plicicollis Sharp, are redescribed and photographs of dorsal views of both sexes are provided. Terminalia of both sexes are illustrated and described for the first time. The Australian Lord Howe Island species, O. simplex White, is transferred from the genus Oemona to Ceresium Newman, and C. procerum Olliff is synonymised with O. simplex. Oemona occurs in both North and South Islands of New Zealand. The phylogenetic analysis suggests that Oemona be divided into two species groups, separata-group and hirta-group.